Factors Affecting Implementation of Integrated AI-Blockchain-IoT in Kenyan Seed Sector - Lilian Cherotich Ronoh; Samuel Mbugua; Richard Ronoh (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Kenyan seed supply chain has made some positive strides towards digitalization of its operations; however, it is still faced with challenges like counterfeit seeds, lack of transparency, lack of traceability, inefficiencies in operations among others. Integration of Blockchain, IoT and AI in the Kenyan seed supply chain has the potential to digitally transform this sector as well alleviate the challenges that the sector is currently facing. However, practical implementation and full uptake of these technologies in Kenyan seed supply chain are hindered by several factors. This study sought to evaluate the factors that affect the successful implementation of integrated AI-Blockchain-IoT in the Kenyan seed supply chain underpinning the TOE model of technology adoption. The target respondents were KALRO and KSC staff from ICT and Seed units as well as farmers and agro-dealers in Tranzoia County. Data collection instruments were questionnaires and interview schedules, and the collected data were analyzed using both descriptive and referential analysis. The findings of this study revealed that high cost of implementation (p = 0.034), limited technical knowledge (p = 0.021), lack of awareness of technology benefits (p = 0.030), reluctance to transition (p = 0.048), and concerns about cost and learning curve (p = 0.020) were found to be statistically significant predictors of lower of AI-Blockchain-IoT adoption.This study helps enlighten the practitioners and the stakeholders in this sector on the various adoption factors to consider as well as highlighting the target areas that need more investments on and interventions.
Keywords: Integrated AI-Blockchain-IoT; Seed Sector; factors; Technology Adoption; TOE